Formic acid as H2 storage system: hydrogenation of CO2 and decomposition of formic acid by solid molecular phosphine catalysts. Issue 18 (10th August 2022) - Kipshagen, Anna; Baums, Janine C.; Hartmann, Heinrich; Besmehn, Astrid; Hausoul, Peter J. C.; Palkovits, Regina
Abstract : The synthesis and decomposition of formic acid (FA) in aqueous triethylamine (NEt3 ) with solid molecular phosphine catalysts is demonstrated. Abstract : The synthesis and decomposition of formic acid (FA) in aqueous triethylamine (NEt3 ) with solid molecular phosphine catalysts is demonstrated. A Ru-catalyst based on the polymeric analog of 1, 2-bis(diphenylphosphino)ethane presented the highest activity with a TON of 9680 under mild reaction conditions. Reaction parameters such as solvent, amine, pressure, time and temperature were systematically investigated. The application as a H2 storage system was demonstrated by coupling both reactions. In recycling experiments, a decrease of the hydrogenation activity was observed, while the decomposition rate remained constant. Characterization of the spent catalyts revealed the formation of carbonyl complexes which are responsible for the observed activity difference.